NURSING TELECONSULTATION FOR PEOPLE WITH SPINAL CORD INJURY: NURSES’ OPINION ON THE MAIN GUIDELINES (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: to identify the opinion of nurses on the main topics to be addressed in the nursing teleconsultation of a telerehabilitation program for spinal cord injuries. Methods: descriptive and exploratory study, carried out with experienced nurses in the rehabilitation of people with spinal cord injuries in a network of rehabilitation hospitals. 70 nurses participated in the study. The data were collected through self-administered questionnaires built on the Google Forms® platform and organized in an Excel® spreadsheet. A descriptive statistical analysis of objective responses and a categorical content analysis of discursive responses were performed. Results: Nurses considered it important to accompany people with spinal cord injuries in the transition from care to home and to provide guidance through social networks, telephones, and/or applications. It was found that the main topics to be addressed in the nursing teleconsultation in a telerehabilitation service are skin care and bladder and bowel reeducation. Conclusions: The nursing teleconsultation allows the exchange of information between the nurse of a specialized rehabilitation service and the person with a spinal cord injury in their home environment, encouraging learning and enabling the person’s co-participation and proactivity in managing their self-care.